РАЗРАБОТКА СИСТЕМЫ УПРАВЛЕНИЯ СОЛНЕЧНЫМ ТРЕКЕРОМ НА БАЗЕ КОНТРОЛЛЕРА АРДУИНО (World Science, 2019)
The panels that track the Sun using a tracker produce 30% more energy (per day) than stationary. The article discusses the development of a solar tracker and its control system based on the Arduino controller. The results of experiments conducted on a stationary panel and a solar tracker are presented. A comparative analysis of the experimental results is presented.